Dalihan Na Tolu Sebagai Pandangan Hidup dalam Menumbuhkan Karakter Anak (Studi Etnografi pada Masyarakat Batak Toba Samosir) - Napitupulu, Aslina; Delzy Perkasa, Ripho; Fauza, Hendri (Indo-MathEdu Intellectuals Journal, 2024)
The primary aim of this research is to delve into the understanding of "dalihan na tolu" as the guiding philosophy in the lives of the Batak Toba community and to examine its practical application within their societal framework. Employing a qualitative approach with an ethnographic orientation, the study incorporates various data collection techniques, including interviews, observations, and documentation. The research involves key informants such as the village head of Parparean III, community leaders, traditional figures, as well as parents and children in Parparean III village, situated in Porsea District, Toba Samosir. The subsequent data analysis encompasses reduction, presentation, verification, and drawing of conclusions. The research findings shed light on several noteworthy points: Firstly, the comprehension of Dalihan Na Tolu as a worldview varies across the community. Traditional figures and community leaders exhibit a clear understanding, whereas parents and children show a diminishing grasp of Dalihan Na Tolu. Secondly, observations during the research highlight the continued application of Dalihan Na Tolu by traditional figures and community leaders. However, there is a discernible decline in its implementation among parents. Lastly, a discernible shift in Dalihan Na Tolu as the societal worldview of the Batak community becomes evident when comparing the past to the present.